2012
DOI: 10.4049/jimmunol.1102899
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Inflammatory MicroRNAs by Ig-like Transcript 3 Is Essential for the Differentiation of Human CD8+ T Suppressor Cells

Abstract: We have investigated the mechanism underlying the immunoregulatory function of membrane Ig-like transcript 3 (ILT3) and soluble ILT3Fc. microRNA (miRNA) expression profile identified genes that were downregulated in ILT3-induced human CD8+ T suppressor cells (Ts) while upregulated in T cells primed in the absence of ILT3. We found that miR-21, miR-30b, and miR-155 target the 3′-untranslated region of genes whose expression was strongly increased in ILT3Fc-induced Ts, such as dual specificity phosphatase 10, B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…The microRNA miR-155 also can regulate expression of other mRNAs encoding other proteins, such as the suppressor of cytokine signaling (SOCS)1, 40,41 transforming growth factor (TGF) b-1, TGF b-2, or TGF b-receptor type 2, which may play a role in tumor invasion and/or metastasis. 42 However, other than INPP5D, none of the known targets of miR-155 encode proteins that can directly influence BCR signaling.…”
Section: Org Frommentioning
confidence: 99%
“…The microRNA miR-155 also can regulate expression of other mRNAs encoding other proteins, such as the suppressor of cytokine signaling (SOCS)1, 40,41 transforming growth factor (TGF) b-1, TGF b-2, or TGF b-receptor type 2, which may play a role in tumor invasion and/or metastasis. 42 However, other than INPP5D, none of the known targets of miR-155 encode proteins that can directly influence BCR signaling.…”
Section: Org Frommentioning
confidence: 99%
“…Together, these data indicate that attenuated common gc cytokine signaling, decreased Akt activation, and aberrant type I IFN signaling likely cooperate to impair the proliferative and survival fitness of miR-155-deficient CD8 + T cells. Additionally, a decreased level of expression of a combination of miR-155, miR-21, and miR-30b in CD8 + T cells is associated with increased expression of SOCS1, DUSP10, and BCL6, all of which are known inhibitors of TCR signaling, which results in impaired CD8 + T cell activation [47,48]. Like miR-155, miR-17 ;92 also seems to be particularly important during the expansion phase, owing to the fact that following LCMV infection, miR-17.…”
Section: Mirna-mediated Regulation Of Cd8 + T Cell Proliferation Surmentioning
confidence: 99%
“…46 In addition to Bach2, it was also reported that the key transcriptional factors controlling the B cell terminal differentiation, Bcl6 and Blimp1, were also the target of miR30b. 47,48 The main function of Bcl6 is to suppress Blimp1 by direct binding to a response element in the prdm1 gene that encodes the Blimp1 protein, 49 and by indirectly suppressing the activation of AP-1 50 and signal transducer and activator of transcription 3 (STAT3), 51 which are both transcriptional activators of Blimp1. Bach2 suppresses B cell terminal differentiation through negatively controlling Blimp1 in B cells 16 and is positively regulated by Pax5, 18 which also represses Blimp1 by directly binding to the prdm1 gene promoter.…”
Section: Discussionmentioning
confidence: 99%